The Influence of Knowledge, Attitude and Behavior of Clean and Healthy Living on Toddler Families in the Working Area of Enarotali Community Health Center, Paniai Regency - Dolianci Pigai; Nur Susan Iriyanti Ibrahim; Bau Kanang (The International Science of Health Journal, 2024)
Background: The direct cause of eating problems in infants is a mismatch between the amount of food that can be digested and the amount of food needed by the baby's body. This may lead to malnutrition and various diseases such as malnutrition and childhood obesity. In addition, illness is also a direct cause of eating problems because the child becomes less hungry to eat.In the Enarotali Health Center Working Area, there are 96 people suffering from malnutrition; toddlers suffering from malnutrition; and the number of toddler families implementing PHBS is 98.3%. Objectives:To find out whether knowledge about cleanliness and health (PHBS) influences the nutritional status of toddlers.in the Enarotali Health Center Working Area, Paniai Regency. Method:The study was conducted using a cross-sectional study approach, in the Enarotali Health Center Working Area, Paniai Regency from April 1 to June 1, 2024. The sampling method used Accidental Sampling, namely 80 toddlers. This research instrument used a questionnaire and anthropometric tools. Data processing was carried out using the SPSS version 16 application. Results: The chi-square test showed that there was an influence of knowledge awareness of cleanliness and hygiene with the nutritional status of toddlers, namely the p-value (0.00) <0.05, attitudes, hygiene behavior and healthy lifestyles with the nutritional status of toddlers had a p-value (0.00) <0.05 and PHBS actions and nutritional status of toddlers had a p-value (0.00). Conclusion: There is an influence between knowledge, attitudes, and PHBS behavior on the nutritional status of toddlers. Suggestion: Mothers who have toddlers should continue to bring their young children to the integrated health post every month. So that if health problems are found in toddlers, they can be treated early.